Participatory Leadership Style of Top Management at Medi Groups Bali - Kharisma, Anak Agung Mira; Satrya, I Dewa Gde (AIBPM Publisher, 2022)
The purpose of the study was to determine the participatory leadership style of the top management of Medi Groups Bali. This research was conducted with a descriptive qualitative approach and data collection by observation and interview. The result of this research is that this participatory leadership style can develop the company because it builds a culture that all teams must actively contribute to every existing process by increasing their work motivation and innovation. The participatory decision-making process at Medi Groups is divided into 2 levels, namely the executive level which produces strategic policies and the operational level which produces decisions in terms of execution. The conclusion of this study is that decisions made through discussions between superiors and subordinates with many studies and inputs from different individuals and different generations make the company able to adapt to current developments and be able to survive in the future.